The influence of self-efficacy and financial literacy on entrepreneurship intention in Medan city - Fransisca Gozelia Boelova; Christine Junita; Kelvin Kosasih; Dwita Sakuntala; Arsyaf Tampubolon (Jurnal Mantik, 2023)
This study aims to provide empirical evidence regarding the effect of self-efficacy and financial literacy on entrepreneurial intentions of entrepreneurs in the city of Medan by testing each variable. The population in this study are all entrepreneurs in Indonesia whose number is not known with certainty and the sample is 384 people. The research method used is multiple linear regression analysis. The results of the calculation of partial hypothesis testing obtained the self-efficacy variable obtained a value of tcount < ttable or -0.601 < 0.05 and a significant obtained 0.548 > 0.05 and financial literacy obtained a value of tcount > ttable or 16.043 > 0.05 and a significant obtained 0.000 < 0.05. So, the self-efficacy variable has no effect on the entrepreneurial intentions of entrepreneurs in the city of Medan and financial literacy has a positive and significant effect on the entrepreneurial intentions of entrepreneurs in Indonesia. Results The calculation results of simultaneous hypothesis testing obtained the value of Fcount (213.628) > Ftable (3.019) with a significance level of 0.000 <0.05. So simultaneously, the variables of self-efficacy and financial literacy have a positive and significant effect on the entrepreneurial intentions of entrepreneurs in Indonesia. The results of the test for the coefficient of determination obtained an R Square value of 0.526. This shows that 52.6% of the variables of self-efficacy (X1) and financial literacy (X2) are able to explain the entrepreneurial intention variable (Y) of entrepreneurs in the city of Medan, the remaining 47.4% are influenced by other variables not examined in this study such as personal financial management, knowledge entrepreneurship, and so on. In summary, the research findings indicate that self-efficacy does not have a significant impact on the entrepreneurial intentions of entrepreneurs in the city of Medan, Indonesia